1994
DOI: 10.1126/science.263.5145.367
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Photorefractive Polymers

Abstract: Photorefractive materials can form "instant" holograms without time-consuming development steps. Their potential applications include image processing, optical data storage, and correction of image distortion, but the cost of crystal growth and preparation has been a primary impediment to commercial application. Polymers, on the other hand, are low in cost and readily fabricated in a variety of forms. Photorefractive polymers were constructed with performance that matched or exceeded the performance of availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…Since the discovery of photorefractive polymers, 1 the response strength, e.g., holographic diffraction efficiency or two-beam energy coupling gain, has improved greatly. [2][3][4][5] However, the speed of response, which is proportional to the photoconductivity, remains unacceptably low for many applications, with best response times in milliseconds ͑at 1 W/cm 2 optical intensity͒. 6,7 The photorefractive speed is proportional to the charge carrier mobility and yet recent studies [8][9][10][11] have revealed that carrier mobilities are greatly suppressed in the presence of dipolar species.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of photorefractive polymers, 1 the response strength, e.g., holographic diffraction efficiency or two-beam energy coupling gain, has improved greatly. [2][3][4][5] However, the speed of response, which is proportional to the photoconductivity, remains unacceptably low for many applications, with best response times in milliseconds ͑at 1 W/cm 2 optical intensity͒. 6,7 The photorefractive speed is proportional to the charge carrier mobility and yet recent studies [8][9][10][11] have revealed that carrier mobilities are greatly suppressed in the presence of dipolar species.…”
Section: Introductionmentioning
confidence: 99%
“…(8). This number is approximately a factor of 5 smaller than the number previously measured for other samples of the same photorefractive polymer composite, 37 possibly a consequence of DEH crystallization with age 22 in this 1-month-old sample.…”
Section: Resultsmentioning
confidence: 58%
“…30 that would take into consideration the pronounced electric field dependence of the charge-carrier generation efficiency and mobility [31][32][33] that has been reported for polymeric systems. 34,35 For this fit we assume that the effective electro-optic coefficient is proportional to the applied electric field, 36,37 as is appropriate for a sample that poles at operating temperature and may also include contributions from orientational gratings. 27 In this geometry we calculate the diffusion field E d ϭ k B TK/e ϭ 0.62 Ϯ 0.01 kV/cm, where K ϭ 2/⌳.…”
Section: Resultsmentioning
confidence: 99%
“…From a practical point of view, the optical amplification, Γ, must exceed the absorption loss, R, of the PR sample in question. [37][38][39] In this case, the optical loss of the sandwiched sample (glass/ITO/polymer composite/ITO/glass) at 1.31 µm was measured to be R ) 4.2 cm -1 yielding a maximum net gain coefficient of Γ -R ) 30.9 cm -1 . An example of asymmetric exchange of energy is depicted in the inset in Figure 3, which confirms the PR nature of the NCPbS composite.…”
Section: Resultsmentioning
confidence: 99%